Smart Ration Card with RFID, Biometrics and Sensors - Thokal, SS; Bhosale, Aarti N; Bhor, Shweta S; Sabale, Pratima K; Shinde, Pushpak R (International Journal of Computer Sciences and Engineering, 2025)
In this paper, our system is based on a smart ration card. In which we have used sensors, Radio frequency identification, bio metrics and OTP (one time password) to achieve security in existing ration allocation system. For maintaining details of family members RFID card is used. User have to provide thumb impression for authentication. If customer found authenticate then he is allowed to take his allocated ration on that particular month.This ration allocated to customer is approved by taluka admin and provided to shopkeeper. Smart ration card is immune to the theft and forgery ,because the information about allocated ration will be send directly to the higher authority(Government), and customer will received information via OTP.A survey conducted for measuring the problem faced by the people on existing Ration Distribution and after that the idea for the Smart Ration Card System is enacted.